PENGEMBANGAN APLIKASI MEDIA PEMILIHAN DESAIN BATIK MAJALENGKA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - ZAPAR SIDIK, SIDIK; BASTIAN, ADE (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The development of information technology is so rapid, allowing the implementation of more efficient ways for the production, distribution, and consumption of goods and services. With the advancement of technology and information, it also makes humans in dealing with other parties as if they are no longer limited by time and place, one of them is mobile marketing based on augmented reality that has high potential to attract users' interests, because it allows users to interact in all contexts of daily life. With that, android based augmented reality application will be made with the MDLC and marker based tracking method. .